2023
DOI: 10.2169/internalmedicine.9666-22
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Myopathy Associated with Anti-mitochondrial Antibody-negative Primary Biliary Cholangitis Diagnosed by a Liver Biopsy

Abstract: Anti-mitochondrial antibody (AMA)-associated myopathies represent a homogeneous disease entity with severe arrhythmia and slowly progressive proximal muscle weakness with lordotic posture, irrespective of the presence of primary biliary cholangitis (PBC). We herein report a case of myositis associated with PBC without AMAs. A 48-year-old woman presented with clinical features very similar to AMA-associated myositis, despite negative AMAs. PBC, ascertained by a liver biopsy performed based on mildly elevated li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…may add important light to the pathophysiology and diagnosis of AIM. AMAassociated myopathies are reported as a homogeneous disease entity with severe arrhythmia and slowly progressive proximal muscle weakness with lordotic posture, features which are irrespective of the presence of primary biliary cholangitis (PBC) [129]. Albayda et al reported a small cohort of seven AIM (DM and PM) with conventional AMA (M2 EP, MIT3) detected by ELISA [128].…”
Section: Cortactinmentioning
confidence: 99%
See 2 more Smart Citations
“…may add important light to the pathophysiology and diagnosis of AIM. AMAassociated myopathies are reported as a homogeneous disease entity with severe arrhythmia and slowly progressive proximal muscle weakness with lordotic posture, features which are irrespective of the presence of primary biliary cholangitis (PBC) [129]. Albayda et al reported a small cohort of seven AIM (DM and PM) with conventional AMA (M2 EP, MIT3) detected by ELISA [128].…”
Section: Cortactinmentioning
confidence: 99%
“…There is considerable interest in the malfunction of mitochondria in AIM and other rheumatic diseases [ 134 ▪ , 135 ] suggesting that the presence of antimitochondrial antibodies (AMA) found in up to 10% of AIM [ 130 ▪▪ ] may add important light to the pathophysiology and diagnosis of AIM. AMA-associated myopathies are reported as a homogeneous disease entity with severe arrhythmia and slowly progressive proximal muscle weakness with lordotic posture, features which are irrespective of the presence of primary biliary cholangitis (PBC) [ 129 ]. Albayda et al reported a small cohort of seven AIM (DM and PM) with conventional AMA (M2 EP, MIT3) detected by ELISA [ 128 ].…”
Section: Anti-mitochondrial Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation